COMPONENT COMPOSITION AND BIOLOGICAL ACTIVITY OF ESSENTIAL OILS OF GENUS DRACOCEPHALUM L. - Suleimen, Yerlan Melsuly; Myrzagaliyeva, Anar Bazarovna; IbatayevZharkyn Аbykenovich; Iskakova, Zhanar Baktybaevna; Samarkhanov, Talant Nurzhakypovich; Medeubayeva, Balzhan Zaruetovna (Химия растительного сырья, 2016)
This article presents data on the study of the chemical composition, antiradical and cytotoxic activity of three species of the genus Dracocephalum L., which grow in East Kazakstan. Essential oils are obtained from aerial parts of plants D. nutans, D. ruyschiana, D. thymiflorum and the average yield of oil was 0,2%. The chemical composition of essential oils were determined by the GC/MS. Cytotoxic activity of essential oils was determined by the survival of Artemia salinaaquatic crustaceans. Essential oils of D. nutans, D. ruyschiana and D. thymiflorum in all concentrations (1–10 mg/mL) tested exhibit acute lethal toxicity – all larvae were died. Antiradical activity was determined by the method based on colorimetry of free radicals (DPPH). The experimental results showed that essential oils from D. nutans, D. ruyschiana and D. thymiflorum at all tested concentrations (0,1–1,0 mg/mL) exhibited low antiradical activity compared with the standard drug – butylhydroxyanisole.